Frequency of Congenital Heart Disease in Patients with Down Syndrome - Ali Shah, Mishkat; Rehman, Habib Ur; Habib, Noor; Ur Rehman, Sijad; Ishaq, Muhammad; Bibi, Romana (Journal of Gandhara Medical and Dental Science, 2023)
OBJECTIVES Frequency of congenital heart disease in patients with Down syndrome. METHODOLOGY This study was conducted in Hayatabad Medical Complex, Peshawar from 10th May 2021 to 9th November 2021. A total of 377 patients of age 1 to 10 years and both gender were included in the study. Those with already diagnosed cases of congenital heart disease and dysmorphic features other than Down syndrome were excluded from the study. All patients were undergone echocardiography and patient with PDA, VSD, ASD, ASVSD, and TOF were labeled as having congenital heart diseases. RESULTS Mean age was 5.96 ±1.954, Males were 176 (46.7%) while females were 201 (53.3%), Mean birth weight was 3.45 ± 0.801 kg, Mean age of the mother was 38.25 ± 6.797 years, Congenital heart diseases were present in 157 (41.6%) of the patient while it was not present in 220 (58.4%) of patients, there was no association between congenital heart disease and age of mother, age of the child, sex of child or weight of the child (P >0.05). CONCLUSION Congenital heart disease is very common in patients with Down syndrome. It is recommended that at the time of diagnosis of this disease, the patient should be screened for congenital heart disease.